Studies on plant regeneration and somaclonal variation in Saintpaulia ionantha Wendl. (African Violet) - Daud, N.; Taha, R.M.; Hasbullah, N.A. (2008)
Efficient plant regeneration of Saintpaulia ionantha (African violet) has been obtained in the present study. MS medium supplemented with 1.0 mg L -1 IAA and 2.0 mg L-1 Zeatin resulted in 100 shoot regeneration and induced the highest number of shoots (average 15.0±0.8 shoots per explant) after being cultured for 8 weeks. The above hormone combination was optimum for shoot regeneration. Most of Saintpaulia ionantha plantlets derived from tissue culture system could be hardened and transferred to the greenhouse conditions with 84.0±1.6 success rate. However, regenerated plantlets of Saintpaulia ionantha (even after 12 months old) failed to flower. Morphological characters of regenerated plantlets of Saintpaulia ionantha were observed and compared with in vivo (intact) plants. Regenerated plantlets showed some differences in morphological characters, such as height and leaf size, texture and colour, but the plantlets showed no variation in leaf arrangement and leaf margin. However, the morphological characters of the regenerated plantlets were found to be unstable. © 2008 Asian Network for Scientific Information.